If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m + 11 = -7(-5 + m) Reorder the terms: 11 + -3m = -7(-5 + m) 11 + -3m = (-5 * -7 + m * -7) 11 + -3m = (35 + -7m) Solving 11 + -3m = 35 + -7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7m' to each side of the equation. 11 + -3m + 7m = 35 + -7m + 7m Combine like terms: -3m + 7m = 4m 11 + 4m = 35 + -7m + 7m Combine like terms: -7m + 7m = 0 11 + 4m = 35 + 0 11 + 4m = 35 Add '-11' to each side of the equation. 11 + -11 + 4m = 35 + -11 Combine like terms: 11 + -11 = 0 0 + 4m = 35 + -11 4m = 35 + -11 Combine like terms: 35 + -11 = 24 4m = 24 Divide each side by '4'. m = 6 Simplifying m = 6
| -7(7n+1)+5n=38+n | | 6(8-7n)+2n=168 | | 10(2x+6)=-4(1+3x) | | 10x+8x=98 | | -30+2x=3(3x+4) | | -4-5n=3(5n-8) | | 45+54+x=180 | | 36+7n=-7+6(4n-7) | | -5(-8x-3)+2=-19+4x | | -3+3x=4(x-3)+7 | | 3x+9+30=105 | | 4x-20x=24 | | 0.5x-1.5=-0.4x-3.6 | | (2×-3)/4=9 | | 30+2x+9+x=180 | | -1/7x=-9 | | 2(x+3)-3=88-3x | | -3+5(m-5)=-20+6m | | 0.5x-1.5=0.4x-3.6 | | y-9=-1/7x | | 103.5=9(m+3.9) | | 4-8x=3(-7x-3) | | 3x-251=1189 | | 75+33x+9=180 | | 16x-23=57 | | 2982=42(p+20) | | 105+105+x=180 | | 4xy+2b-(3xy)-5b= | | 3x+9+x+x=180 | | 3x+20=2x-40+2x+20 | | -3+8m=11-4-2m | | 15a+5b=255 |